MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN 1 SAMPAI 10 MELALUI MEDIA POHON BILANGAN BAGI ANAK TUNAGRAHITA RINGAN - Netti - Hartati (Jurnal Penelitian Pendidikan Khusus, 2013)
The purpose of this study was to: 1) Know the process of learning the concept of number 1 to number 10 in the media tree. 2) Prove that if the number of media use trees to improve the ability to know the concept of numbers 1 to 10 on a class II mild mental retardation children in Al-Ishlaah Sebereng Padang. This type of research is a class act (classroom action research) that takes the form of collaboration with colleagues at two research subjects, namely children D.II. grade mild mental retardation. Data obtained through observation and tests. Then analyzed qualitatively quantitatively. The results showed that 1) the process of learning the concept of number 1 to number 10 in the media tree done in two cycles. 2) The study showed that: Cycle I know the concept of numbers (reading, naming and sorting) numbers from 1 to 10 value RN (100) and AT (93.3). While the current assessment value of RN (40) and AT (43.3). Cycle II familiar concept of numbers (to match the number of objects and write) numbers from 1 to 10 value RN (90) and AT (80). While the current assessment value of RN (10) and AT (5). It can be concluded that, overall, an increase in the ability of the concept of numbers from 1 to 10 children D.II grade mild mental retardation in SLB Al-Ishlaah Seberang Padang through the media tree numbers. Suggested schools, teachers and researchers to use the next number in the media tree membelajarkan tunagrahita child is in familiar concept of numbers.